Prognostic significance of preoperative albumin to fibrinogen ratio associated nomograms in patients with breast invasive ductal carcinoma. Issue 26 (26th June 2020) - Zheng, Lihua; Zhao, Yaheng; Liu, Feng; Liu, Peng; Li, Wei; Yang, Yan; Zhang, Hongsong; Liu, Yunjiang
Abstract : Abstract: Plasma albumin to fibrinogen ratio is involved in human cancer, but its prognostic significance in breast cancer is controversy. In the context of breast invasive ductal carcinoma, this research aims to retrospectively evaluate by preoperative plasma albumin to fibrinogen ratio (AFR) and forecast oncological outcome and recurrence. This retrospective study comprised 230 patients with non-metastatic breast invasive ductal carcinoma who underwent surgery between January 2009 and April 2012 in Fourth Hospital of Hebei Medical University. Patients were categorized base on an optimal value of preoperative plasma fibrinogen (Fib) and albumin. Progression-free and cancer-specific survival were assessed using Kaplan–Meier method. The associations between albumin to fibrinogen ratio and clinical outcomes were assessed with univariate and multivariate analysis. A number of risk factors were used to form nomograms to evaluate survival, and Harrell concordance index (C-index) was used to evaluate the predictive accuracy. Plasma AFR was significantly associated with diminished disease-free survival (DFS) and overall survival (OS). Multivariate analysis revealed that plasma AFR was an independent prognostic indicator for DFS (HR = 1.346; 95% CI: 1.107–1.636; P  = .03) and overall survival (OS) (HR = 1.485; 95% CI: 1.106–1.993; P  = .008). Two prediction model of 3-, 5-years OS and DFS based on the AFR was developed. Elevated preoperative plasma AFR is an independent prognostic factor for oncological outcomes in patients with breast invasive ductal carcinoma. The formulated nomogram showed superior predictive accuracy for DFS and OS.